Modelling and Simulation CO2-Emissions of a Product (From Cradle-to-Grave) early in Design - Hamza Bassam (2023)
As the global temperature increases continually, the demand for methodologies that support the development of sustainable systems becomes more and more important. Under these circumstances, industries are forced to become sustainable in order to compete successfully against ecologically acting market participants. This work supports these industries interested in developing complex sustainable systems. It is also bene cial for both the Life Cycle Assessment (LCA) and Model-Based Systems Engineering (MBSE) communities. This work develops an MBSE methodology that supports the modelling and Simulation of the environmental aspect of a product from cradle-to-grave in early design stages, when changes are easy and incurred costs are low. It extends the V-Model to consider all life cycle stages and assigns a V for each stage. The left wing of the V, which represents early design stages, is separated with regard to the Requirements, Functions, Logic and Physics (RFLP) approach. The LCA stages are allocated to each level of the RFLP approach. This work demonstrates the methodology using a SysML model of the robot Engineering Living Systems in Automation (ELSA). The model encompasses all life cycle stages that are representative for cradle-to-grave. The results show that MBSE can support in managing the complexity, better understanding the problem, ease the communication of information and analysis throughout the life cycle of a product. The SysML Model provides a way to navigate through the different life cycle stages and hierarchies to study the system. One can go from a top-level perspective and further narrow the scope in order to identify the critical elements. Once a critical element is identifed, the traceability relationships other a chain, where in each step of it a possibility for changing the design is offered. This offers a way to analyze the life cycle of a product in early design stages, when incurred costs are low and changes are easy. Since the main focus of this work is to develop a methodology that shows WHAT to do, HOW to do it and demonstrate the HOWs using a tool. Due to the time constraint of a master thesis, the scope was compromised from one life cycle stage to another in order to include all stages that are representative for cradle-to-grave. Therefore, future work could validate the methodology in order to assess the effort needed to implement it and the benefit from it. Furthermore, the circular economy strategies could be integrated in future research in order to close the cycle from cradle-to-cradle.
Keywords: Life Cycle Assessment; Model Based Systems Engineering; Systems Modeling Language; Product Life Cycle; Cradle-to-Grave